Microfabricated ferromagnetic-shape-memory Heuslers: The geometry and size effects. (June 2021) - Takhsha Ghahfarokhi, Milad; Arregi, Jon Ander; Casoli, Francesca; Horký, Michal; Cabassi, Riccardo; Uhlíř, Vojtěch; Albertini, Franca
Highlights: Microfabrication of ferromagnetic-shape-memory epitaxial films along different substrate directions allows a selective twin formation. Lateral size, shape and geometry modifications are exploitable for microstructure engineering of ferromagnetic-shape-memory microfabricated structures. Ferromagnetic shape memory materials are exploitable for micro-scale applications; magnetostructural properties are perfectly preserved under lithographic microfabrication. Abstract: Ferromagnetic-shape-memory (FSM) Heuslers are a class of smart materials, promising for integration into miniaturized thermo/magnetomechanical devices, applicable in automotive, aerospace, biology, and robotics fields. In addition to compactness and mechanical simplicity, it is crucial for the material to maintain its properties at micro and nanometer scales. This study evidences the effects of lateral dimension and geometry on the properties of FSM Heuslers in patterned epitaxially grown Ni-Mn-Ga films. In particular, arrays of microstructures with lateral sizes down to the micrometer range, having different shapes and orientations with respect to the substrate edges, are investigated. The key properties of the material are stable after the microfabrication process: the martensitic transition temperatures increase by less than 3 K and thermal hysteresis changes by only 2 K. Notably, the size and geometry (i.e. shape and orientation) of the patterned microstructures are reported to be a suitable tool for controlling the martensitic configuration. The study demonstrates selective response of a specific type of martensitic twin boundaries, i.e., X-type twin boundaries along [110] MgO and [1–10] MgO, to the shape and orientation of the microstructures showing a twin boundary selection of up to ~96%. The effects of lateral size, shape, and orientation on the martensitic and magnetic properties of the lithographically patterned structures are discussed.